Hypoxemia in Young Children Undergoing One-lung Ventilation: A Retrospective Cohort Study. (20th September 2021) - Templeton, T. Wesley; Miller, Scott A.; Lee, Lisa K.; Kheterpal, Sachin; Mathis, Michael R.; Goenaga-Díaz, Eduardo J.; Templeton, Leah B.; Saha, Amit K.
Abstract : Background: One-lung ventilation in children remains a specialized practice with low case numbers even at tertiary centers, preventing an assessment of best practices. The authors hypothesized that certain case factors may be associated with a higher risk of intraprocedural hypoxemia in children undergoing thoracic surgery and one-lung ventilation. Methods: The Multicenter Perioperative Outcomes database and a local quality improvement database were queried for documentation of one-lung ventilation in children 2 months to 3 yr of age inclusive between 2010 and 2020. Patients undergoing vascular or other cardiac procedures were excluded. All records were reviewed electronically for the presence of hypoxemia, oxygen saturation measured by pulse oximetry (Spo 2 ) less than 90% for 3 min or more continuously, and severe hypoxemia, Spo 2 less than 90% for 5 min or more continuously during one-lung ventilation. Records were also assessed for hypercarbia, end-tidal CO2 greater than 60 mmHg for 5 min or more or a Paco 2 greater than 60 on arterial blood gas. Covariates assessed for association with these outcomes included age, weight, American Society of Anesthesiologists (Schaumburg, Illinois) Physical Status 3 or greater, duration of one-lung ventilation, preoperative Spo 2 less than 98%, bronchial blocker versus endobronchial intubation, left operative side, video-assisted thoracoscopic surgery, lower tidal volume ventilation (tidal volume less than or equal to 6 ml/kg plus positive end expiratory pressure greater than or equal to 4 cm H2 O for more than 80% of the duration of one-lung ventilation), and type of procedure. Results: Three hundred six cases from 15 institutions were included for analysis. Hypoxemia and severe hypoxemia occurred in 81 of 306 (26%) patients and 56 of 306 (18%), respectively. Hypercarbia occurred in 153 of 306 (50%). Factors associated with lower risk of hypoxemia in multivariable analysis included left operative side (odds ratio, 0.45 [95% CI, 0.251 to 0.78]) and bronchial blocker use (odds ratio, 0.351 [95% CI, 0.177 to 0.67]). Additionally, use of a bronchial blocker was associated with a reduced risk of severe hypoxemia (odds ratio, 0.290 [95% CI, 0.125 to 0.62]). Conclusions: Use of a bronchial blocker was associated with a lower risk of hypoxemia in young children undergoing one-lung ventilation. Abstract : In a retrospective multisite cohort study in children aged 2 months to 3 yr having one-lung ventilation for thoracic surgery, hypoxemia was common. Bronchial blocker use as well as left-sided surgeries were associated with a lower risk of hypoxemia during one-lung ventilation. Supplemental Digital Content is available in the text.